Driving Employee Productivity: Commitment, Training, and Performance Analysis: Mengungkap Katalisator Produktivitas Karyawan: Analisis Komitmen, Pelatihan, dan Kinerja Kerja - Meyga Putri Cahyana; Hasan Ubaidillah (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to investigate the influence of employee commitment, training, and work performance on employee productivity. Employing a quantitative research design, data were collected from a sample of 117 employees, drawn from a population of 176 individuals, using a non-probability sampling technique. The analysis of the data revealed that employee commitment, training, and work performance each had a partially positive effect on employee productivity. These findings highlight the significance of fostering employee commitment, providing effective training programs, and emphasizing the importance of high work performance to enhance overall employee productivity. The implications of these results shed light on the factors that can optimize employee productivity within organizations and provide valuable insights for practitioners and researchers alike. Highlights: Employee commitment, training, and work performance significantly impact productivity. Quantitative research methods reveal the relationship between these variables. The study emphasizes the importance of optimizing commitment, training, and work performance to enhance productivity. Keywords: Employee productivity, Commitment, Training, Work performance, Quantitative research.